Evaluating the Impact of Increased Precipitation on UK Grassland Ecosystems and Soil Carbon Sequestration - Zhao Xuanyi (MATEC Web of Conferences)
Climate-driven alterations in precipitation patterns increasingly threaten the sustainability of temperate grasslands, yet the ecological impacts of sustained rainfall increases remain poorly understood. This review addresses the core question: how do prolonged increases in precipitation influence soil carbon sequestration, plant community structure, and ecosystem functioning in UK grasslands? Through a systematic synthesis of recent experimental, observational, and modeling studies, we clarify the mechanisms underlying grassland responses to persistent wetter conditions, define critical ecological thresholds, and identify varied ecosystem sensitivities across different landscapes. Our findings demonstrate that while moderate increases in rainfall can enhance soil carbon storage and plant productivity, excessive and sustained precipitation often leads to soil waterlogging, shifts toward anaerobic microbial processes, reduced biodiversity, and diminished ecosystem resilience. We propose targeted strategies for adaptive management, including improving drainage infrastructure in vulnerable regions, selecting plant species with diverse functional traits to maintain resilience, and establishing robust long-term monitoring programs. This integrative analysis provides essential guidance for land managers and policymakers to sustain grassland ecosystem services under future climate scenarios.